Antibacterial activity and characterization of endophytic bacteria from selected medicinal plants of Malaysia - Mohamed Rafi, Mohamed Ikhtifar (2018)
Malaysia is blessed with rich biodiversity and her people have harnessed this virtue in many ways such as for medicinal uses. However, not all of the plants could be easily grown or harvest for its bioactive natural products for use. Endophytes which are microorganisms that live in plants could be the key in solving this conundrum. Many past studies have shown that endophytes could have the same properties as the host and proven to produce anti-bacterial or anti-cancer compounds. The aims of this study is to characterize the endophytic bacteria isolates which has been isolated from known medicinal plants such as Senna obtusifolia (SK 2283/13), Leea indica (SK 2285/13), Pereskia sacharosa (SK 2286/13) and Isotoma longiflora (SK 2288/13) according their phenotypic traits and genotypic traits. The phenotypic traits that were taken into consideration were the isolation media, the parts of the plants that the isolates were isolated from, the growth conditions such growth rate and temperature, type of gram, antibiogram profile of the isolates, anti-bacterial susceptibility test against bacterial pathogens. The genotypic traits were deduced by using Random Amplification of Polymorphic DNA (RAPD). This study have found that the highest number of isolates were isolated from Senna obtusifolia and the highest number of isolates that were isolated are from the roots of the plants. The best isolation media to be used for isolating the isolates is Starch-Casein Agar. 36 isolates were gram negative and 27 isolates were gram positive in nature. In this study, it was discovered that most of the isolates were susceptible towards Chloramphenicol and resistant towards Gentamicin. The dichloromethane extracts of 28 bacterial isolates shown inhibition towards 9 bacterial pathogens which are Acinobacter baumanii, Bacillus cereus, Bacillus subtilis, Enterobacter cloacae, Klebsiella pneumonia, MRSA, Proteus vulgaris, Salmonella Paratyphi A and Staphylococcus aureus. For the genotypic traits, the genomic DNA of the isolates were amplified successfully by using Primers OPO 10 and OPO 16. In conclusion, the endophytic bacteria isolates were characterized by their phenotypic and genotypic traits and it was found that 9 single isolates clusters which were (ATC)DB3-B, (PDA)IB(B1)-B, (PDA)IF(B1)- B, (SCA)FSe(B1)-B, (PDA)IS(B1)-B, (SCA)IL(B1)-B and (ATC)IF(B1)-B were unique based on both phenotypic and genotypic traits of the isolates.